The Students’ Perception Toward Online Discussion in a Threaded Online Platform - Dhimas Dwi Nugraha Hadistya (Jurnal Linguistik Terapan, 2024)
This study follows up students' perception to threaded online discussions from private university in Malang, East Java, Indonesia. This study was conducted on a sample space of 45 undergraduate Civil Engineering students who were all aged between 18 to 24 years. The participants included 13 females and 32 and they were then broken out into six groups to read the material and discussed in in the threaded online discussion through ProBoard platform. It employed a mixed-method approach and the interaction level were examined based on Thomas’ framework. Six students were interviewed in Bahasa Indonesia using semi-structured interviews to ensure that responses are clear. Interviews and questionnaires showed that 13 students experienced technical problems on the online platform. The atmosphere and communication matters played significant roles in eliciting unfavourable perceptions of the students in terms of online discussion. A follow-on examination indicates that in general, students do not like threaded discussions. However, the study also indicated that there is potential for online discussion to be used in language learning setting.